The 1624 Tumult of Mexico in perspective (c. 1620-1650) : authority and conflict resolution in the Iberian Atlantic - Ballone, Angela (European expansion and indigenous response ;, 2018)
The 1624 Tumult of Mexico in Perspective proves that, despite the various conflicts underlying the disturbances in New Spain between circa 1620 and 1650, there was no intention to do away with the authority of the king.